The effects of sprint (300 m) running on plasma lactate, uric acid, creatine kinase and lactate dehydrogenase in competitive hurdlers and ultrained men - Klapcinska, B.; Iskra, J.; Poprzecki, S.; Grzesiok, K. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND High intensity exercise may induce muscle damage especially in individuals unaccustomed to regular physical efforts. Our aim was to compare the impact of 300 m sprint running on muscle enzymes release into blood in competitive hurdlers and untrained but physically fit adults. METHODS: EXPERIMENTAL DESIGN: comparative study. SETTING: general community. PARTICIPANTS: nine competitive hurdlers (CH; 21.3 yrs+/-3.1) and six matched moderately active untrained men (UT). INTERVENTIONS: subjects performed a single 300 m sprint running test. MEASURES: plasma creatine kinase (CK) and lactate dehydrogenase (LD) activities, and concentrations of lactate (LA) and uric acid (UA) measured before the warm-up and 5 min, 2 and 20 hrs postrun. RESULTS: Mean runner performance achieved by CH was significantly better (35.53-s+/-0.64) and LA concentrations significantly higher (14.95 mM+/-0.59) than those recorded in UT (41.52-s+/-2.22; 10.13 mM+/-0.59). Pre- and postrun CK activities until the 2nd hour of recovery were found to be significantly higher (p<0.05) in CH than in UT, whereas LD activities were similar in both groups pretest, but significantly higher in UT immediately postrun. In CH, the highest CK activity (32 percent; increase) was recorded immediately post-test, whereas in UT the peak CK (135 percent; increase) was attained in the 20th hour of recovery. In both groups UA reached the peak level in the 2nd hour of recovery. CONCLUSIONS: More pronounced and delayed postrun increase in CK, as recorded in UT, may provide evidence of a larger exercise-induced muscle injury in the untrained adults. Higher postexercise UA levels as recorded in CH might account for a more marked involvement of adenylate kinase reaction in ATP resynthesis.